Effects of Enteral Fluid Therapy in Continuous Flow Administered by Nasogastric Tube in Buffalo Calves - Ermita, Pedro A.N.; Viana, Rinaldo B.; Ribeiro Filho, José D.; Guimarães, José D.; Dias, Domingos C.R.; Monteiro, Bruno M.; Monteiro, Lorena C.; Moreira, Alef R.P.; Mendonça, André A.N.; Ferreira, Ana C.O.; Bremgartner, Liane do S.; Ribeiro, Bruna M.; et al. (Journal of Buffalo Science, 2016)
To investigate the employment of enteral fluid therapy in continuous flow administered by a nasogastric tube in buffalo calves; toassesstheeffectsof a hypotonic and an isotonic electrolyte solutionon: vital functions, blood count and serum andurinary biochemistry profile of buffalo calves. Seven buffalo calves, clinically healthy, were submitted to two treatments. The solutions were administered in continuous flow through a nasogastric tube at a dose of 15 mL/kg/hr for 12 hours. The serum biochemistry profile showed an increase in chloride concentration, decrease in serumurea and osmolarity. In urine, anincrease in sodium and chloride concentrations and a decrease in calcium, creatinine and urea were observed. Enteral fluid therapy in continuous flow proved to beeasy to use and effective in maintaining volemia and concentration of electrolytes in buffalo calves